Callose balancing at plasmodesmata. (28th August 2018) - Wu, Shu-Wei; Kumar, Ritesh; Iswanto, Arya Bagus Boedi; Kim, Jae-Yean
Abstract : Callose is a key plasmodesmal marker molecule that controls the permeability of plasmodesmata. The callose level is fine-tuned by the orchestration of upstream regulators under stress conditions and during plant development. Abstract: In plants, communication and molecular exchanges between different cells and tissues are dependent on the apoplastic and symplastic pathways. Symplastic molecular exchanges take place through the plasmodesmata, which connect the cytoplasm of neighboring cells in a highly controlled manner. Callose, a β-1, 3-glucan polysaccharide, is a plasmodesmal marker molecule that is deposited in cell walls near the neck zone of plasmodesmata and controls their permeability. During cell differentiation and plant development, and in response to diverse stresses, the level of callose in plasmodesmata is highly regulated by two antagonistic enzymes, callose synthase or glucan synthase-like and β-1, 3-glucanase. The diverse modes of regulation by callose synthase and β-1, 3-glucanase have been uncovered in the past decades through biochemical, molecular, genetic, and omics methods. This review highlights recent findings regarding the function of plasmodesmal callose and the molecular players involved in callose metabolism, and provides new insight into the mechanisms maintaining plasmodesmal callose homeostasis.